Structural and Technological Principles in Architecture Curriculum of Eastern Mediterranean University in Northern Cyprus - Mokhaberi, Ghazaleh (ICONARCH International Congress of Architecture and Planning, 2012)
Architecture pedagogy has various aspects and requirements. To achieve a successful architectural teaching system there is a need for giving sufficient attention to structural stability and technical issues of buildings from one hand and noticing aesthetical concems of architecture from the other hand. Curricula of architecture schools play a critical role in this regard. The ability of integrating technical and structural aspects of building design into other design disciplines can be given to students by appropriate considerations within the architecture curricula. This survey indicates and highlights the necessary basic requirements of structural thoughts for every architecture curriculum and architecture curriculum of Eastem Mediterranean University (EMU) has been specifically focused; it sefficiency in terms of teaching of structural principles has been examined through some questionnaires and interviews. Accordingly, some comparisons with the existing literatures and also curricula of well-known universities from around the world have been done; consequently, some suggestions are made to increase the efficiency of EMU curriculum in term s of teaching of structural concepts. In fact, the research is a contribution towards updating the architecture curriculum of EMU according to the latest structural and technological requirement softhe contemporary architectural education.